2012
DOI: 10.1074/jbc.m112.401406
|View full text |Cite
|
Sign up to set email alerts
|

Toll or Interleukin-1 Receptor (TIR) Domain-containing Adaptor Inducing Interferon-β (TRIF)-mediated Caspase-11 Protease Production Integrates Toll-like Receptor 4 (TLR4) Protein- and Nlrp3 Inflammasome-mediated Host Defense against Enteropathogens

Abstract: Background: C. rodentium and E. coli induce noncanonical Nlrp3 inflammasome activation through caspase-11. Results: TLR4-TRIF are important for caspase-11 expression, caspase-1 activation, and downstream IL-1␤ and IL-18 production. Conclusion: TLR4-TRIF axis plays an important role in the up-regulation of caspase-11 and activation of noncanonical inflammasome. Significance: Our study identifies novel molecules upstream of caspase-11 that are involved in activation of noncanonical inflammasome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
208
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 222 publications
(211 citation statements)
references
References 40 publications
(39 reference statements)
2
208
0
1
Order By: Relevance
“…Thus, all of the noncanonical caspase-1 activation pathways described so far converge at the point of NLRP3 activation (12,13,18,19), which is consistent with NLRP3 being capable of integrating signals from different microbial agonists. We predict that, similar to the canonical caspase-1 signaling pathways, caspase-11 activation requires an upstream protein(s) capable of sensing a microbial or endogenous danger signal.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Thus, all of the noncanonical caspase-1 activation pathways described so far converge at the point of NLRP3 activation (12,13,18,19), which is consistent with NLRP3 being capable of integrating signals from different microbial agonists. We predict that, similar to the canonical caspase-1 signaling pathways, caspase-11 activation requires an upstream protein(s) capable of sensing a microbial or endogenous danger signal.…”
Section: Discussionmentioning
confidence: 50%
“…Casp1/11 -/- 13, 18,19). By contrast, Legionella activated the caspase-11-dependent pathway within 4 h of infection, which suggested that activation of caspase-11 could occur by different pathways depending on the bacterial agonist.…”
Section: Discussionmentioning
confidence: 91%
“…LPS-stimulated bone marrow-derived macrophages (BMDMs) of caspase-11 -/-mice were defective in IL-1β secretion when exposed to cholera toxin b (CtB) or when infected with Gram-negative enteropathogens such as C. rodentium, Vibrio cholerae and E. coli (Kayagaki et al, 2011). Subsequent studies demonstrated that caspase-11 expression and activation downstream of Toll-like receptor 4-(TLR) and TIR-domain-containing adapter-inducing IFN-β (TRIF)-dependent production of type I interferons contributed to IL-1β production by a broad array of Gramnegative bacterial pathogens (Broz et al, 2012;Gurung et al, 2012;Rathinam et al, 2012). In contrast, caspase-11 was dispensable for IL-1β secretion by Gram-positive bacteria.…”
Section: Caspase-11: a Cytosolic Sensor Of Lipopolysaccharidesmentioning
confidence: 99%
“…It is implicated in host defence against a wide range of bacterial (Staphylococcus aureus, Escherichia coli, Citrobacter rodentium) (He et al, 2010;Gurung et al, 2012), viral (influenza A) (Allen et al, 2009;Thomas et al, 2009), fungal (Candida albicans, Aspergillus fumigates; Gross et al, 2009) and parasitic (Leishmania amazonensis) infections (Lamkanfi and Dixit, 2012;Lima et al, 2013). In addition, the Nlrp3 inflammasome is activated by damage-associated molecular patterns (DAMPs) such as adenosine triphosphate (ATP), uric acid crystals, amyloid β fibrils and hyaluronan that are thought to trigger inflammation under sterile conditions.…”
Section: The Nlrp3 Inflammasomementioning
confidence: 99%
“…In addition to the canonical inflammasome, cytosolic LPS or infection by Gramnegative bacteria triggers a caspase-11-containing noncanonical inflammasome (16)(17)(18). This noncanonical inflammasome induces GSDMD-mediated cell death and IL-1␣ secretion independently of caspase-1 in response to caspase-11-mediated sensing of cytosolic LPS (14,15,(19)(20)(21).…”
mentioning
confidence: 99%